A STUDY OF THE IMPACT OF MAXIMUM AND MINIMUM PARENTAL INTERVENTION ON THE LEARNING STYLES OF THEIR CHILDREN - Kaur, Shaminder; Sharma, Madhu (International Journal of Research -GRANTHAALAYAH, 2025)
Humans are social beings. They strive for self-improvement within society through their actions and reactions. This improvement can only be achieved when they begin to apply the eternal values ​​of their culture and civilization in their daily lives. In the present era, education is no longer limited to the school; the role of the family and parents in the overall personality development of the child has become extremely important. The extent to which parents intervene in their child’s studies, decisions, and behavior directly impacts the child’s learning style. The parenting practices adopted by parents influence the child’s learning behavior. Differences in the child’s learning style can arise depending on the level of parental intervention. This study was conducted to examine this fact and to clarify the relationship between parental intervention and learning style.